Ruminal colonization and potential of Megashaera elsdenii NCIMB 41125 to stimulate rumen development and its effects on the performance of pre-weaned Holstein calves - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.